Efektivitas Rekayasa Komposter Semi Anaerob Skala Rumah Tangga - Sawir, Hendri; Mariza Syahyuda, Nelsy (Riset Sinergi Indonesia, 2022)
Composter Engineering. The research method uses the treatment of the number of semi-anaerobic composter oxygen channels with 3 different oxygen holes. The results showed that the lowest temperature was obtained on repetition 1 for composter 6 holes with a temperature of 31.64°C and the highest for repetition 2 on composter 8 holes were 32.85°C. The lowest pH was obtained on repetition 1 for composter 10 holes with a pH of 5.66 and the highest for repetition 3 on composter 6 holes was 6.55. The results of the characteristics of compost fertilizer were obtained from the analysis of time, water content, phosphorus (P2O5), potassium, carbon, nitrogen, and C/N ratio. The conclusion was obtained, a semi-anaerobic composter was produced with 3 types of holes, namely 6 holes, 8 holes, and 10 holes with a composter tube capacity of 60 liters, having dimensions of 40 cm in diameter with a height of 60 cm and for the time the composter obtained the ideal compost was a composter with several holes the most is 10 holes with the results obtained which are 15-16 days compared to 6 holes 28 days and 8 holes 23 days. It is recommended to use materials that are not too wet which will inhibit the rate of decomposition and the presence of a pungent odor.